Preparation and Sustained-Release Performance of PLGA Microcapsule Carrier System - Shuaikai Ren (Nanomaterials, 2021)
Microcapsules have been widely studied owing to their biocompatibility and potential for application in various areas, particularly drug delivery. However, the size of microcapsules is difficult to control, and the size distribution is very broad via various encapsulation techniques. Therefore, it is necessary to obtain microcapsules with uniform and tailored size for the construction of controlled-release drug carriers. In this study, emulsification and solvent evaporation methods were used to prepare a variety of ovalbumin-loaded poly (lactic-co-glycolic acid) (PLGA) microcapsules to determine the optimal preparation conditions. The particle size of the PLGA microcapsules prepared using the optimum conditions was approximately 200 nm, which showed good dispersibility with an ovalbumin encapsulation rate of more than 60%. In addition, porous microcapsules with different pore sizes were prepared by adding a varying amount of porogen bovine serum albumin (BSA) to the internal water phase. The release curve showed that the rate of protein release from the microcapsules could be controlled by adjusting the pore size. These findings demonstrated that we could tailor the morphology and structure of microcapsules by regulating the preparation conditions, thus controlling the encapsulation efficiency and the release performance of the microcapsule carrier system. We envision that this controlled-release novel microcapsule carrier system shows great potential for biomedical applications.